1990
DOI: 10.3109/07853899009147234
|View full text |Cite
|
Sign up to set email alerts
|

Tetanus in Finland: Diagnostic Problems and Complications

Abstract: In a 16-year nationwide study in Finland 106 patients were diagnosed as having tetanus. Tetanus was diagnosed on the first visit to a doctor in half the patients, it was suspected in 28% but not considered in 22%. Diagnosis of tetanus may be delayed if a patient is elderly or has no known primary lesion. Abnormal EEGs and CSF findings with increased protein level were unexpectedly common (76% and 24% respectively). The most significant complications were cardiac arrhythmias (34%), blood pressure lability (32%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
5

Year Published

1992
1992
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
0
5
0
5
Order By: Relevance
“…The association of so called milder forms i.e. stages I and II on Ablett's criteria [3] to ANS dysfunction and its affect on outcome is not well established. Our study highlights the importance of this previously not well-known aspect of tetanus.…”
Section: Introductionmentioning
confidence: 99%
“…The association of so called milder forms i.e. stages I and II on Ablett's criteria [3] to ANS dysfunction and its affect on outcome is not well established. Our study highlights the importance of this previously not well-known aspect of tetanus.…”
Section: Introductionmentioning
confidence: 99%
“…2,16 It was shown that tetanus had been diagnosed on the first visit to a doctor in only half of the patients, suspected in 28% and not considered in 22%. 4 The main problems are difficulty of early diagnosis and treatment of severe complications. There is a need for prompt diagnosis and treatment because of the risk of respiratory failure.…”
Section: Discussionmentioning
confidence: 99%
“…3 The main problem facing emergency physicians is the difficulty in early diagnosis of this uncommon disease. 4,5 This is the report of a case of tetanus with subtle initial presentation.…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of tetanus is likely to be delayed if a patient is elderly or has no known primary lesion 3 . The worst prognosis occurs in infants, the elderly, smokers and those with grossly contaminated wounds and a short period of onset of symptoms.…”
Section: Discussionmentioning
confidence: 99%